Animal Acts : Performing Species Today - Hughes, Holly, 1955 March 10-; Chaudhuri, Una, 1951- (Book collections on Project MUSE., 2014)
"Everyone has an animal story--the pet they loved or hated, the wild animal that captured their childhood imagination, the nasty dog at the end of the street, the deer your uncle shot or your neighbor hit while driving. Telling stories about animals is part of how we tell the story of being human, but recent scientific breakthroughs in animal cognition, the exploding interdisciplinary field of animal studies, and global climate change have all complicated these stories. Animal Acts collects some of the most exciting, provocative, and moving solo performances on animals, grounded by commentaries that help put these engaging works in a larger context. Animal Acts includes the work of leading theater artists Holly Hughes, Rachel Rosenthal, Deke Weaver, Carmelita Tropicana, and others, along with commentary by major scholars including Donna Haraway, Jane Desmond, Jill Dolan, and Nigel Rothfels. A masterful introduction by Una Chaudhuri provides readers a useful foundation for understanding and appreciating the intersection of animal studies and performance. The anthology makes an important contribution to several fields as it foregrounds questions of race, gender, sexuality, class, nation, and other issues central to the human project within the discourse of the "post human." The collection will be of interest to those interested in solo performance, animal studies, gender studies, performance studies, and environmental studies"--